Myostatin and follistatin expression in skeletal muscles of rats with chronic heart failure - Ruiz Lima, Aline Regina [UNESP]; Martinez, Paula Felippe [UNESP]; Okoshi, Katashi [UNESP]; Guizoni, Daniele Mendes [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Salome Campos, Dijon Henrique [UNESP]; Oliveira, Silvio Assis [UNESP]; Bonomo, Camila [UNESP]; Dal Pai-Silva, Maeli [UNESP]; Okoshi, Marina Politi [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
P>Skeletal muscle abnormalities can contribute to decreased exercise capacity in heart failure. Although muscle atrophy is a common alteration in heart failure, the mechanisms responsible for muscle mass reduction are not clear. Myostatin, a member of TGF-beta family (transforming growth factor), regulates muscle growth and mass. Several studies have shown a negative correlation between myostatin expression and muscle mass. The aim of this study was to evaluate myostatin expression in skeletal muscles of rats with heart failure. As myostatin gene expression can be modulated by follistatin, we also evaluated its expression. Heart failure was induced by myocardial infarction (MI, n = 10); results were compared to Sham-operated group (n = 10). Ventricular function was assessed by echocardiogram. Gene expression was analyzed by real-time PCR and protein levels by Western blotting in the soleus and gastrocnemius muscles; fibre trophism was evaluated by morphometric analysis. MI group presented heart failure evidence such as pleural effusion and right ventricular hypertrophy. Left ventricular dilation and dysfunction were observed in MI group. In the soleus muscle, cross-sectional area (P = 0.006) and follistatin protein levels (Sham 1.00 +/- 0.36; MI 0.18 +/- 0.06 arbitrary units; P = 0.03) were lower in MI and there was a trend for follistatin gene expression to be lower in MI group (P = 0.085). There was no change in myostatin expression between groups. In gastrocnemius, all MI group parameters were statistically similar to the Sham. In conclusion, our data show that during chronic heart failure, decreased skeletal muscle trophism is combined with unchanged myostatin and reduced follistatin expression.
Keywords: cardiac failure; follistatin; myocardial infarction; myostatin; PCR; skeletal muscle